Syed Husin Ali’s socio-political thoughts and contributions - Zamri, Zahid; Omar, Muhamad Fuzi (IIUM Press, 2017)
The book attempts to look into the historical background of Syed Husin Ali’s political and academic activities, the major socio-political thoughts that exist within his works, how his ideas have influenced the political principles of the opposition parties, what has shaped his socio-political thoughts and the similarities or differences that those ideas have with Western or Eastern political thoughts. The study chooses the qualitative method to analyse the discourse. We used qualitative content analysis in our attempt to extract political ideas from the collected data. The primary sources are his major works, where we extracted his socio-political thoughts. Then, we referred to his documented and non-documented party speeches and his party’s political principles and manifesto, in order to see how those thoughts are channelled towards his party. Other sources such as open-ended interviews and discussions, articles, press statements, and tabloids published by the newspapers that are associated with him are taken as supportive documents. The book finds that four of the concepts that he has always highlighted in his writings as well as speeches, namely neo-feudalism, neo-colonialism, poverty and ethnic-based politics are developed based on the concept of elitism, and the concept of elitism that he uses is to some extent similar to Gramsci’s concept of bourgeois hegemony, thus rejecting the claim that he is an orthodox Marxist or leans towards Weberian. In addition, it is undeniable that he was also influenced by the ideas of the three Malay nationalists namely Dr. Burhanuddin al-Helmy, Ahmad Boestamam and Pak Sako.